Phāprūam sētthakit kānkhā kap prathēt ph̄ưanbān Thai-S̜̄oP̜̄oP̜̄o. Lāo dān phāk Tawanʻ̜̄ok Chiang N̄ưa (Samnakngān Phānit Čhangwat N̨̄ong Khāi, 1997)
Trade with neighboring countries and economy around the Thai-Lao Friendship Bridge, Northeastern Thailand.